E-Commerce Growth and Its Impact on Logistics Performance, Service Quality, and Customer Experience in Indonesia - Purnomo Purnomo; Fenny Damayanti; Rosalina Rosalina (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This study aims to analyze the impact of e-commerce growth on logistics performance, service quality, and customer experience in Indonesia. Based on Service-Dominant Logic (SDL), this study explores the role of logistics capabilities in creating customer value amidst the rapid growth of the digital commerce ecosystem. Methodology: The study employed a mixed-methods explanatory design. Quantitative data were collected from 150 e-commerce consumers and analyzed using AMOS-based Structural Equation Modeling (SEM). Qualitative data were obtained through interviews with logistics practitioners to strengthen and validate the quantitative results. Findings: The findings indicate that e-commerce growth has a significant positive effect on logistics performance. Logistics performance has also been shown to improve service quality, and service quality has a positive impact on customer experience. Furthermore, service quality mediates the relationship between logistics performance and customer experience. This indicates that operational capabilities create customer value through service perceptions. Conclusion: Qualitative results highlight the importance of last-mile delivery innovation, transparency, responsiveness, and service recovery in building trust and customer experience. This study adds to the SDL literature by demonstrating that logistics performance is a strategic resource whose value is realized through service quality. These findings are also relevant for e-commerce companies and logistics providers in emerging digital markets.